Gasoline Quality Monitoring Via Vehicle OBD Data Analysis - Ismail, Nurul Aqilah (Universiti Sains Malaysia, 2018)
Research octane number (RON) determines the quality of knocking resistance of a fuel in a spark ignition (SI) engine. In Malaysia, the most commonly found petrol fuel types are RON95 and RON97. One of the objectives of this research project is to compare the engine performance of the vehicle by studying the spark ignition of the engine when it is fuelled with gasoline fuel of different octane number and from the different petrol station. The comparative analysis spark advance timing with research octane number (RON) 95, and 97 was carried out on a Perodua Myvi SE 2017 under different types of gasoline fuels available in the Parit Buntar town. The different gasoline fuels consist of Caltex, Petron, Petronas and Shell. The results showed a special pattern for each fuel RON; these patterns were obtained using the spark advance timing, throttle/ load applied to the vehicle and the speed the vehicle is driven. The results are then further proved with SHATOX SX-200 portable octane tester to read the actual RON reading of the sample of the gasoline fuels. Different petrol stations alter their fuel differently. This explains the different reading obtained as the gasoline fuels are tested with the portable octane tester.